The other krill: overwintering physiology of adult Thysanoessa inermis (Euphausiacea) from the high‑Arctic Kongsfjord - K Huenerlage (Inter-Research, 2015)
Polar environments like the high-Arctic Kongsfjord are characterized by pronounced seasonality leading to strong variations in primary production. Food sources are particularly scarce during winter. Herbivorous krill, such as the arcto-boreal Thysanoessa inermis, are key components in the ecosystem of Kongsfjord and strongly rely on phytoplankton as a food source. During the polar night such species must therefore be adapted to survive long periods without significant nutritional input. We investigated physiological mechanisms and the allocation of energy resources to try to explain how T. inermis manages to survive the Arctic winter. Adult specimens caught in late summer were kept under starvation conditions for 28 d. Changes in metabolic rates (respiration and excretion) and biochemical composition (protein, lipid and fatty acid analyses) were monitored. In contrast to the Antarctic krill Euphausia superba and the subtropical E. hanseni, the arcto-boreal species did not reduce metabolism but utilized lipid reserves for survival. Assessed from total lipid stores and energy demand, the potential survival period was estimated at 63 d without food uptake, which is not sufficient to survive the entire winter. Results were compared to specimens that overwintered in situ and were discussed in relation to other euphausiids. In conclusion, T. inermis is well adapted to survive the Arctic winter provided that alternative food sources are available, but has a different strategy to cope with starvation than krill species from other latitudes.